Nationality, Protection, and 'the Country of His Nationality' as the Country of Reference for the Purposes of Article 1A(2) of the 1951 Convention relating to the Status of Refugees. (18th October 2021) - Fripp, Eric
Abstract: The 1951 Convention relating to the Status of Refugees assumes States to be dominant actors in the international system, important in the refugee law context as potential sources of risk and/or of protection. In the refugee definition at article 1A(2), the nationality (or absence of nationality) of the individual is a central consideration. Entitlement to protection turns in significant part upon whether an individual is 'outside the country of his nationality' and 'unable or … unwilling to avail himself of the protection of that country' for relevant reason. The phrase 'the country of his nationality' is clarified later, in the second paragraph of that article 1A(2), as meaning each country of nationality, where an individual possesses more than one nationality. In contrast, an individual 'not having a nationality' is assessed by reference to inability or unwillingness, for qualifying reason, 'to return to' a country defined by past residence, not nationality – 'the country of his former habitual residence'. This article examines the underlying significance of States to international refugee law as potential sources both of threat and of protection, and considers the article 1A(2) definition in the case of persons with a nationality, resting on the individual's position as regards 'the country of his nationality'. In doing so, it identifies particular national approaches that have treated the concept either as including countries of which an individual is not a national, but to which there is some presumed or real relationship, or as inapplicable to a State of nationality that does not provide a particular level of protection. It then considers the interpretation of the article 1A(2) definition in the case of individuals possessing multiple nationality and, in particular, whether the definition requires that a well-founded fear of persecution for relevant reason must relate directly to every country of nationality before a right to international protection arises.